Fabrication of alumina based electrically conductive polymer composites. Issue 5 (29th September 2015) - Nadeem, QuratulAin; Rizwan, Muhammad; Gill, Rohama; Rafique, Muhammad; Shahid, Muhammad
ABSTRACT: Novel electrically conductive composites were synthesized by incorporating Cu coated alumina (Cu‐Al2 O3 ) powder prepared via electroless plating technique as filler (0–21wt %) into polystyrene‐ b ‐methylmethacrylate (PS‐ b ‐PMMA) and polystyrene (PS) matrices. XRD analysis depicted maximum Cu crystallite growth (26.116 nm∼ plating time 30 min) onto Al2 O3 along with a significant change in XRD patterns of composites with Cu‐Al2 O3 inclusion. SEM–EDX analyses exhibited uniform Cu growth onto Al2 O3 and confirmed presence of Cu, Al, Pd in Cu‐Al2 O3, and C, O, Al, Cu, and Pd in PS‐ b ‐PMMA and PS composites. Increasing filler loadings exhibited increased electrical conductivity (5.55 × 10 −5 S/cm for PS‐ b ‐PMMA; 5.0 × 10 −6 S/cm for PS) with increased Young's modulus (1122MPa for PS‐ b ‐PMMA; 1053.9MPa for PS) and tensile strength (27.998MPa for PS‐ b ‐PMMA; 30.585MPa for PS) and decreased % elongation. TGA demonstrated increased thermal stability and DTG revealed two‐step degradation in composites while DSC depicted pronounced increment in Tg of Cu‐Al2 O3 /PS‐ b ‐PMMA with increased filler loading. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42939. Abstract :